HEMANGIOBLASTOMA SEREBELUM - Bhaskoro Adi Widie Nugroho, I komang Arimbawa, I Gusti Ngurah Purna Putra (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION HEMANGIOBLASTOMA ACCOUNTS FOR 2 OF ALL INTRACRANIAL NEOPLASMS AND BECAME THE MOST COMMON PRIMARY ADULT INTRAAXIAL POSTERIOR FOSSA TUMOR THIS TUMOR CAN OCCUR SPORADICALLY OR ASSOCIATED WITH VON HIPPELLINDAU DISEASE VHL THE TREATMENT FOR CNS HEMANGIOBLASTOMA USUALLY INCLUDE RESECTION OF SYMPTOMATIC TUMOR BY PREOPERATIVE ARTERIAL EMBOLIZATION